Inhibiting myostatin signaling prevents femoral trabecular bone loss and microarchitecture deterioration in diet-induced obese rats - Tang, Liang (Exp Biol Med (Maywood), 2015)
Besides resulting in a dramatic increase in skeletal muscle mass, myostatin (MSTN) deficiency has a positive effect on bone formation. However, the issue about whether blocking MSTN can inhibit obesity-induced bone loss has not been previously investigated. In the present study, we have evaluated the effects of MSTN blocking on bone quality in high-fat (HF), diet-induced obese rats using a prepared polyclonal antibody for MSTN (MsAb). Twenty-four rats were randomly assigned to the Control, HF and HF + MsAb groups. Rats in the HF + MsAb group were injected once a week with purified MsAb for eight weeks. The results showed that MsAb significantly reduced body and fat weight, and increased muscle mass and strength in the HF group. MicroCT analysis demonstrated that obesity-induced bone loss and architecture deterioration were significantly mitigated by MsAb treatment, as evidenced by increased bone mineral density, bone volume over total volume, trabecular number and thickness, and decreased trabecular separation and structure model index. However, neither HF diet nor MsAb treatment had an impact on femoral biomechanical properties including maximum load, stiffness, energy absorption and elastic modulus. Moreover, MsAb significantly increased adiponectin concentrations, and decreased TNF-α and IL-6 levels in diet-induced obese rats. Taken together, blocking MSTN by MsAb improves bone quality in diet-induced obese rats through a mechanotransduction pathway from skeletal muscle, and the accompanying changes occurring in the levels of circulating adipokines and pro-inflammatory cytokines may also be involved in this process. It indicates that the administration of MSTN antagonists may be a promising therapy for treating obesity and obesity-induced bone loss.